(untitled) (Fiep Bulletin - online, 2013)
The Physical Education, for several decades, proved remiss in posing questions of a political, economic, cultural and social. However, when social issues related with the scientific advances of this educational component, it is unacceptable that the pedagogical practice proves unrelated issues postmodern. Thus, this study aims to discuss the need for effective educational practice of physical education toward the democratization of an education that values ??the different cultural manifestations of students. Therefore, we sought to correlate the theoretical critical multiculturalism with discussions raised by a critical reality, so we can elucidate the educational praxis requires a reordering level conceptual, procedural and attitudinal teachers, so that processes construction of students’ identities are not adulterated their ethnicity, and that students are critical so that they no longer are hostages of a political cultural ideological alienating. In this perspective, it is of paramount importance that the teacher is aware of the various forms of selection and presentation of content, which, depending on the policy option may serve to maintain the status quo of hegemonic culture, or demystify stereotypes, stigmas and prejudices about cultures historically stifled, forming citizens freed from ethnocentrism, in that culture body related to specific cultural events, steeped in its identity, is valued.